PENGARUH PERBEDAAN LABA AKUNTANSI DAN LABA FISKAL TERHADAP PERSISTENSI LABA DENGAN KOMPONEN AKRUAL DAN ALIRAN KAS SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2008-2011) - Fatkhur Haris Irfan; Endang Kiswara (Diponegoro Journal of Accounting, 2013)
This research aimed to analyze factors that lead to book tax differences, and then analyze the effect of book tax differences to earnings persistence, and the ability to analyze the accrual component in influencing of earnings persistence on the listed manufacturing companies in Indonesia Stock Exchange during years 2008-2011. In this research, there were two dependent variables, five independent variables, and two moderating variables. The dependent variable in this study consisted of book tax differences, and earnings persistence. The independent variable of this study consisted of large negative and positive book tax differences, the changes in revenues, the value of gross fixed assets, and firm size. Moderating variables of this study consists of accruals and cash flow components. Methods of statistical analysis in this study is multiple regression analysis using the program Eviews 6.0.The results of this research indicated that the changes in revenues, and the gross value of fixed assets a positive effect on book tax differences. large positive book tax differences and moderation accrual components with large negative book tax differences effected lower earnings persistence, and moderation accrual components with large positive book tax differences efected higher earnings persistence. This research aims to study materials related to book tax differences, and earnings persistence.